1987
DOI: 10.1021/bi00398a025
|View full text |Cite
|
Sign up to set email alerts
|

Location and activity of ubiquinone 10 and ubiquinone analogs in model and biological membranes

Abstract: Deuteriated analogues of ubiquinone 10 (Q10) have been dispersed with plasma membranes of Escherichia coli and with the inner membranes of beetroot mitochondria. Orientational order at various deuteriated sites was measured by solid-state deuterium nuclear magnetic resonance (2H NMR). Similar measurements were made, using the compounds dispersed in dimyristoylphosphatidylcholine (DMPC) and egg yolk lecithin and dispersions prepared from the lipid extracts of beetroot mitochondria. In all cases only a single un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 33 publications
5
35
0
Order By: Relevance
“…The aggregates are probably interspersed among the hydrocarbon tails of phosholipids, in the hydrophobic membrane core, so that their presence does not modify the lipid main-phase transition. This is in agreement with the deuteron NMR studies by Cornell et al (1987), who found that ubiquinone-10 in lipid bilayers appeared to be in a mobile environment, without orientational constraints. The ubiquinone-10 molecules are aggregated, and not dissolved in the hydrocarbon phase, since, as stated, in the latter case the C = 0 band would be located at 1670 cm-'.…”
Section: The Physical State Of Ubiquinone-10 In Phospholipid Bilayerssupporting
confidence: 92%
See 1 more Smart Citation
“…The aggregates are probably interspersed among the hydrocarbon tails of phosholipids, in the hydrophobic membrane core, so that their presence does not modify the lipid main-phase transition. This is in agreement with the deuteron NMR studies by Cornell et al (1987), who found that ubiquinone-10 in lipid bilayers appeared to be in a mobile environment, without orientational constraints. The ubiquinone-10 molecules are aggregated, and not dissolved in the hydrocarbon phase, since, as stated, in the latter case the C = 0 band would be located at 1670 cm-'.…”
Section: The Physical State Of Ubiquinone-10 In Phospholipid Bilayerssupporting
confidence: 92%
“…The latter opinion is supported by experiments of ferricyanide reduction by dithionite via ubiquinone-containing bilayers (GomezFernandez et al, 1981) and by measurements of fluorescence quenching Lenaz, 1988). In addition, it should be noted that the segregation of ubiquinone-I 0 into separate domains has been postulated by various authors (Hauska, 1977;Michaelis and Moore, 1985;Ulrich et al, 1985;Quinn and Katsikas, 1985;Aranda et al, 1986;Ondarroa and Quinn, 1986b;Cornell et al, 1987). The subject of the physical states of ubiquinone-10 has been addressed by means of X-ray diffraction studies (Quinn and Katsikas, 1985;Lis et al, 1989); various crystalline and isotropic phases have been proposed.…”
mentioning
confidence: 92%
“…Quinone mobility below the transition temperature was also observed in NMR experiments (67). More generally, NMR studies from various groups support the view that the long chain quinones form a specific phase in the membrane, with different mobility and isotropy properties compared with those of the lipids (67)(68)(69).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the need to recognize the isoprenoid region of ubiquinone may be minimal since the ubiquinone headgroup could provide a high degree of binding specificity; this is certainly the case with the photosystem II complex that contains two ubiquinone-binding sites (28,29). This hypothesis is also supported by the finding that long-and short-chain ubiquinones function in electron transport, suggesting that recognition of the isoprenoid chain of ubiquinone is not needed for efficient catalysis (30).…”
Section: Discussionmentioning
confidence: 97%